Tindakan Tiongkok Dalam Mengoptimalisasi Health Security Pada Penanganan Covid-19 (Studi Kasus: Teknologi Artificial Intelligence Tiongkok) - Dyah Ayu Rahmasari; Ika Riswanti Putranti; Muhammad Faizal Alfian (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Health safety issues are becoming a crucial issue right now. An example of a health security issue that is currently threatening global health security is the COVID-19 pandemic. As the first country infected with COVID-19, China was able to reduce the spread of COVID-19 within 4 months and play an active role in improving global health security. The research seeks to figure out China's efforts to optimize the health security dimension for handling COVID-19 in 2020 both regionally and globally. This research method uses a qualitative method that using the concept of health security. Researchers also use secondary data collection methods such as library studies, video analysis and number-based data. The result of this research show that the actions taken by China to optimize the dimensions of health security regionally and globally are based on comprehensive statements delivered by President Xi Jinping which became the basis for China to play an active role to solve COVID-19 and collaborate with various multi sector and multi stake-holder parties which focus on providing support for handling and prevention from the transmission of the COVID-19 pandemic.